PENGARUH LINGKUNGAN KERJA DAN KOMITMEN TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT KOMISI PEMILIHAN UMUM KABUPATEN LAMPUNG TIMUR - Andy Fitriyadi Dharma Tilaar (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2018)
Thus the productivity and employment results of employees will increase optimally. Because theperformance performed affects the effectiveness of organizational performance so to create a highperformance, it needs an optimal work enhancement and able to utilize the potential human resourcespossessed by employees for organizational goals can be achieved, so that will contribute positively tothe development of the organization. In addition, the organization needs to pay attention to variousfactors that may affect the performance of employees, in this case required the role of leaders to createa work environment and commitment to encourage the creation of attitudes and actions professionals incompleting the work in accordance with their respective fields and responsibilities. The phenomenonthat occurs and attract the authors to examine and further review by testing and analyzing the extent towhich